RETRACTED: Development of monitoring of the stress-strain state of the Luzhniki stadium to ensure safe and reliable reconstruction for the 2018 FIFA World Cup - Farfel M. I.; Vdovenko A. I. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001